CHAMFER DISTANCE ON THE FOUR-DIMENSIONAL FACE-CENTRED CUBIC GRID - Turgay, Neset Deniz; Nagy, Benedek; Kovacs, Gergely; Vizvari, Bela (Publ House Bulgarian Acad Sci, 2023)
Chamfer distances are step-based distances on various grids. The four-dimensional FCC grid is the extension of the usual face-centred cubic grid into four dimensions. There are two types of steps, and thus, two weights are used. Operational research, namely linear programming and Gomory cut are applied to describe optimal paths and hence, their weighted lengths, the chamfer distance.
Keywords: lattices; shortest paths; operational research; nontraditional grids